Spatial and Structural Analysis of Futuristic Urban Utopian Thoughts in Climate Change Dystopias - Adnan Oğuzhan; Cenk Hamamcıoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
It is thought that climate change will radically affect societies in the future, leading to radical changes in the structural and spatial mechanisms of cities. Today, most of the World, particularly 10% of the World's population living in settlements below the sea level are expected to be affected by extreme climatic conditions such as sea-level rise, change in ocean currents, destructive weather events and heat waves (IPCC, 2019). As discussed in the literature (see. Hjerpe & Linner, 2009; Foust, 2009), in this study, the most severe effects of climate change are described as a dystopian period. In this direction, the study aims to share and discuss the samples of futurist urban utopia thoughts for the environments such as floating, underwater/sub aqua, underground/subterranean and overhead/aerial (sky, space), which are considered as uninhabitable or difficult to live under normal conditions together with their structural and spatial properties, in order for societies to survive in the dystopia of climate change. In the context of climate change, the futurist urban utopias, which are envisaged for different environments, are analyzed through four variables; technological features, ways of obtaining resources, spatial and urban form conceptions, and their mutual evaluation determined as the method in the study.